ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI EFFECTIVE TAX RATE PADA PERUSAHAAN YANG TERDAFTAR DI BEI - Jony Jony (Universitas Pelita Harapan Medan Campus, 2020)
This research aims to determine factors of Effective Tax Rate in Manufacture Sector companies at Bursa Efek Indonesia. This research will limited Independent variable only for Debt to Asset Ratio, Size of Company, and Return on Asset. The population of this research are all consumer goods sector. Total amount of our observation are 87, come from 29 companies dan 3 years in row, from 2016 to 2018. This research use Double Regression Analysis for its model and use Purposive Sampling method. Data were analyzed by SPSS Software version 26, with 5% significance level. Result of this research showed informations : as partially, Debt to Asset has positive impact and no significant effect on Effective Tax Ratio; Size of Company has negative impact and significant effect on Effective Tax Ratio; Return On Asset has positive impact and no significant effect on Effective Tax Ratio. Simultaneously, all of this factors has positive impact and no significant effect on Effective Tax Ratio.Keywords :DAR, Size Company, ROA, Effective Tax Rate